2003
DOI: 10.1007/s11910-003-0084-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of nonconventional magnetic resonance imaging techniques in demyelinating disorders

Abstract: The use of nonconventional magnetic resonance imaging techniques (eg, magnetization transfer, magnetic resonance spectroscopy, and diffusion weighted imaging) allows for an accurate characterization of lesions as compared with conventional or standard approaches in demyelinating diseases. Magnetization transfer, magnetic resonance spectroscopy, and diffusion weighted imaging have revolutionized our understanding of demyelinating diseases because these techniques have been used to identify pathologic changes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…WM lesion load, however, is only weakly correlated with the disability of patients with MS. 1,2 Given the limited sensitivity of conventional MR imaging, researchers oriented their focus also to subtle damage to the so-called normal-appearing WM (NAWM) and normalappearing gray matter (NAGM), aiming to better explain neurologic impairments of these patients. 3,4 Postmortem and in vivo studies have demonstrated that the deep gray matter (GM) is also affected in MS. Diffuse microscopic damage in the absence of macroscopic MS lesions can be present in the thalamus and basal ganglia. 5,6 The thalamus, in particular, is a critical structure for a wide range of neurologic functions, including motor, sensory, and cognitive abilities.…”
mentioning
confidence: 99%
“…WM lesion load, however, is only weakly correlated with the disability of patients with MS. 1,2 Given the limited sensitivity of conventional MR imaging, researchers oriented their focus also to subtle damage to the so-called normal-appearing WM (NAWM) and normalappearing gray matter (NAGM), aiming to better explain neurologic impairments of these patients. 3,4 Postmortem and in vivo studies have demonstrated that the deep gray matter (GM) is also affected in MS. Diffuse microscopic damage in the absence of macroscopic MS lesions can be present in the thalamus and basal ganglia. 5,6 The thalamus, in particular, is a critical structure for a wide range of neurologic functions, including motor, sensory, and cognitive abilities.…”
mentioning
confidence: 99%
“…An additional limitation of conventional MRI sequences is their inability to identify the effects of MS worsening beyond visible lesions or detecting pre‐lesion formation in CNS tissue appearing as normal. For many years, using non‐conventional quantitative MRI techniques 3 greatly aided in uncovering and quantifying pathology of normal‐appearing CNS tissue. Non‐conventional MRI techniques, however, may be labor‐intensive, thus often difficult to use in daily clinical practice.…”
mentioning
confidence: 99%
“…MTI provides a distinct contrast by measuring the exchange of magnetization between free, mobile protons with the bound, macromolecular protons in tissues [10]. MTI is accomplished by applying an off-resonance radiofrequency pulse to selectively saturate the pool of protons in the bound components of tissue [11]. By comparing the signal intensity using the applied offresonance pulse with that without the pulse, a magnetization transfer ratio (MTR) can be determined.…”
Section: Mtimentioning
confidence: 99%